Juvenile xanthogranuloma as a new type of skin lesions in tuberous sclerosis complex - Qian Lu; Xiu-Yu Shi; Yang-Yang Wang; Meng-Na Zhang; Wen-Ze Wang; Jing Wang; Qiu-Hong Wang; Hui-Min Chen; Li-Ping Zou (Orphanet Journal of Rare Diseases, 2020)
Abstract Objective Tuberous sclerosis complex (TSC) is a rare autosomal dominant genetic disease with many manifestations, and it involves any organ. In this study, we report a TSC patient with new type skin lesions. Methods A 7-month-old TSC boy with multiple cutaneous nodules was admitted in our hospital. We collected the clinical data of the patient. We performed biopsy of cutaneous nodules and whole-exome sequencing in both paraffin block tissue and blood samples. Results The patient presented with a 2 month history of gradual growth multiple cutaneous nodules. He had cardiac rhabdomyoma, subependymal giant cell astrocytoma (SEGA) and hypomelanotic macules. The pathological finding of cutaneous nodules was consistent with juvenile xanthogranuloma (JXG). After 3 months of sirolimus treatment, the multiple nodules disappeared. The whole-exome sequencing identified TSC1 (c.2356C > T, p.R786*) mutation in both paraffin block tissue and blood samples. We overturned the original pathological diagnosis and finally identified JXG as a new type of skin lesions in TSC. Conclusion This is the first report on the occurrence of JXG skin lesions in TSC patient. Genetic testing is necessary in JXG. These findings expand the phenotype of skin in patients with TSC and contribute to the elucidation of JXG pathogenesis and treatment.